Inhibitory effects of anthracyclines on partially purified 5′–3′ DNA helicase of Plasmodium falciparum - Rattaprasert P. (2023)
Background: Plasmodium falciparum has been becoming resistant to the currently used anti-malarial drugs. Searching for new drug targets is urgently needed for anti-malarial development. DNA helicases separating double-stranded DNA into single-stranded DNA intermediates are essential in nearly all DNA metabolic transactions, thus they may act as a candidate for new drug targets against malarial parasites. Methods: In this study, a P. falciparum 5′ to 3′ DNA helicase (PfDH-B) was partially purified from the crude extract of chloroquine- and pyrimethamine-resistant P. falciparum strain K1, by ammonium sulfate precipitation and three chromatographic procedures. DNA helicase activity of partially purified PfDH-B was examined by measuring its ability to unwind 32P-labelled partial duplex DNA. The directionality of PfDH-B was determined, and substrate preference was tested by using various substrates. Inhibitory effects of DNA intercalators such as anthracycline antibiotics on PfDH-B unwinding activity and parasite growth were investigated. Results: The native PfDH-B was partially purified with a specific activity of 4150 units/mg. The PfDH-B could unwind M13-17-mer, M13-31-mer with hanging tail at 3′ or 5′ end and a linear substrate with 3′ end hanging tail but not blunt-ended duplex DNA, and did not need a fork-like substrate. Anthracyclines including aclarubicin, daunorubicin, doxorubicin, and nogalamycin inhibited the unwinding activity of PfDH-B with an IC50 value of 4.0, 7.5, 3.6, and 3.1 µM, respectively. Nogalamycin was the most effective inhibitor on PfDH-B unwinding activity and parasite growth (IC50 = 0.1 ± 0.002 µM). Conclusion: Partial purification and characterization of 5′–3′ DNA helicase of P. falciparum was successfully performed. The partially purified PfDH-B does not need a fork-like substrate structure found in P. falciparum 3′ to 5′ DNA helicase (PfDH-A). Interestingly, nogalamycin was the most potent anthracycline inhibitor for PfDH-B helicase activity and parasite growth in culture. Further studies are needed to search for more potent but less cytotoxic inhibitors targeting P. falciparum DNA helicase in the future.